Visual and corneal biomechanical changes after femtosecond laser-assisted intracorneal ring segment implantation in patients with keratoconus - Paula S Abdel Malek (Delta Journal of Ophthalmology, 2020)
Purpose The aim of this study was to evaluate the effect of femtosecond laser-assisted intrastromal corneal ring segment (ICRS) implantation in patients with keratoconus on the visual outcome and corneal biomechanics using CORVIS ST. Patients and methods This is a prospective interventional study that was carried out on 30 keratoconic eyes which underwent femtosecond laser-assisted ICRS implantation. All the included eyes were assessed before ICRS implantation for uncorrected/best-corrected visual acuity, Pentacam and Corvis ST imaging. They were assessed again at 1 and 3 months after the implantation for the same parameters. Results The mean age of the studied group was 24.00±3.80 years. The uncorrected corrected visual acuity improved significantly at the first (0.36±0.04, P<0.001) and third month (0.53±0.09, P<0.001) after ICRS implantation compared with the preoperative level (0.22±0.05), whereas the best-corrected visual acuity at the third postoperative month (0.73±0.12) was significantly better than the preoperative value (0.60±0.29, P=0.082) and the first postoperative month value (0.60±0.08, P<0.001). The corneal biomechanical index measured by CORVIS ST remained stable from the preoperative level (1.0) till the first month after ICRS implantation but decreased significantly at the third postoperative month to 0.86. There were no significant changes regarding Applanation 1 (A1) or Applanation 2 (A2) times but A1 and A2 lengths and biomechanically corrected intraocular pressure decreased significantly at the first and third month after ICRS implantation than the preoperative level. Conclusion Implantation of ICRS in eyes with keratoconus improved visual acuity and changed significantly the corneal biomechanical parameters measured by CORVIS ST. Corneal biomechanical index, A1, and A2 were significantly decreased with no changes in A1 or A2 times. ICRS implantation can be considered safe, as the complications were almost nil.